The politics of income inequality in the United States - Kelly, Nathan J. (Cambridge University Press, 2009)
This book revolves around one central question: do political dynamics have a systematic and predictable influence on distributional outcomes in the United States? The answer is a resounding yes. Utilizing data from mass income surveys, elite surveys and aggregate time series, as well as theoretical insights from both American and comparative politics, Kelly shows that income inequality is a fundamental part of the US macro political system. Shifts in public opinion, party control of government and the ideological direction of policy all have important consequences for distributional outcomes. Specifically, shifts to the left produce reductions in inequality through two mechanisms - explicit redistribution and market conditioning. Whereas many previous studies focus only on the distributional impact of redistribution, this book shows that such a narrow strategy is misguided. In fact, market mechanisms matter far more than traditional redistribution in translating macro political shifts into distributional outcomes.